The Appreciation of Cryptocurrency: A Study on Digital Asset Knowledge among Rural Bank Personnel in the Second District of Albay Province - Ng, Jefferson; Nasser, Theresa (JPAIR Multidisciplinary Research, 2022)
The COVID-19 pandemic is a modern problem brought about by ease in travel, advanced trade and industry, and the like. This global health concern requires solutions to limit face-to-face interactions, such as cryptocurrency. The researcher makes an effort to use less fiat, which results in paperless transactions. With this system already in place, this study examined how rural bank personnel appreciate cryptocurrency. This study used the descriptive research design and an online survey as its data gathering tool. The respondents were regular employees of rural banks in the second district of Albay who consented to participate in the study. The statistical methods used in the study were the Kendall Coefficient of Concordance W and Chi-square. The findings are the following: the rural banks’ managers were less appreciative of cryptocurrency, and supervisors and office staff felt indecisive about their appreciation. Also, there is a significance of agreement among the respondents in terms of knowledge, regardless of rank. In general, the respondents were not ready to understand and accept cryptocurrency. This study recommends further research to involve other professionals in Albay. The rural bank personnel may also attend webinars regarding digital assets and cryptocurrency. It also recommends the collaboration of banks to improve cryptocurrency appreciation and related concerns.